KEABSAHAN PENGGUNAAN MEREK DAGANG INDOMARET OLEH PELAKU USAHA LAIN DI WILAYAH HUKUM KABUPATEN BANGLI - I Dewa Agung Gede Bagus Trisna Sanjaya; Si Ngurah Ardhya; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the legitimacy and clarity of the use of the Indomaret trademark in Bangli Regency and the legal consequences of using a trademark that is not based on a license in Bangli Regency. The research method used is empirical legal research with the nature of descriptive research. The research location is located in Kintamani District, Bangli Regency with the object of research being two modern stores, Cahaya Mart and Tanaka Mart, which have indications of similarity in principle to the Indomaret trademark. Data collection techniques used were document studies, observations and interviews. The sampling technique used is the Non Probability Sampling technique and the determination of the subject uses Snowball Sampling. Qualitative data processing and analysis techniques. The results of the study show that the use of the Indomaret brand by other parties in the jurisdiction of Bangli Regency is declared valid through an agreement between business actors and Indomaret in accordance with what has been regulated in articles 41 and 42 of Law Number 20 of 2016 concerning Marks and Geographical Indications. Also, other business actors whose validity is declared in using the Indomaret trademark do not get legal consequences or are not required to be responsible for the provisions of article 83 of Law Number 20 of 2016 which states that registered Mark Owners and/or registered Mark Licensees can file a lawsuit against other parties who unlawfully uses a Mark that is similar in principle or in its entirety for similar goods and/or services in the form of a claim for compensation; and/or termination of all actions related to the use of the Mark.